Accumulation of VH Replacement Products in IgH Genes Derived from Autoimmune Diseases and Anti-Viral Responses in Human - Lange, Miles D.; Huang, Lin; Yu, Yangsheng; Li, Song; Liao, Hongyan; Zemlin, Michael; Su, Kaihong; Zhang, Zhixin (Frontiers in Immunology, 2014)
VH replacement refers to RAG-mediated secondary recombination of the IgH genes, which renews almost the entire VH gene coding region but retains a short stretch of nucleotides as a VH replacement footprint at the newly generated VH-DH junction. To explore the biological significance of VH replacement to the antibody repertoire, we developed a Java-based VH replacement footprint analyzer (VHRFA) program and analyzed the distribution of VH replacement products in 61851 human IgH gene sequences downloaded from the NCBI database. The initial assignment of the VH, DH, and JH gene segments provided a comprehensive view of the human IgH repertoire. To our interest, the overall frequency of VH replacement products is 12.1%; the frequencies of VH replacement products in IgH genes using different VH germline genes vary significantly. Importantly, the frequencies of VH replacement products are significantly elevated in IgH genes derived from different autoimmune diseases, including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and allergic rhinitis, and in IgH genes encoding various autoantibodies or anti-viral antibodies. The identified VH replacement footprints preferentially encoded charged amino acids to elongate IgH CDR3 regions, which may contribute to their autoreactivities or anti-viral functions. Analyses of the mutation status of the identified VH replacement products suggested that they had been actively involved in immune responses. These results provide a global view of the distribution of VH replacement products in human IgH genes, especially in IgH genes derived from autoimmune diseases and anti-viral immune responses.